Assessment of Rabies Control Attitudes During the COVID-19 Pandemic through Partial Least Square-Structural Equation Modeling - Purnama, Sang Gede; Utami, Ni Wayan Arya; Subrata, Made; Pradnyani, Putu Erma; Agustina, Karang; Swacita, IBN (UI Scholars Hub, 2023)
The COVID-19 pandemic disrupts rabies control activities in the community. A new approach is needed to control rabies during the COVID-19 pandemic through digital health interventions by conducting digital surveillance and education. This study aimed to determine key attitude indicators in controlling rabies during the COVID-19 pandemic. A cross-sectional study on 166 participants in Denpasar City with a total of 31 indicators measuring five variables: perceptions of the benefits of rabies control (6 indicators), perceptions of rabies risk (6 indicators), perceptions of obstacles to rabies control (5 indicators), perceptions of the need for technology (7 indicators), and attitudes toward rabies control (7 indicators) were analyzed using partial least square-structural equation modeling. The results revealed that 80.7% of participants owned a dog, and sources of rabies information were from social media (45%), the internet (33.7%), and rabies volunteers (33%). The model explained that perception of the benefits of rabies control and the need for technology had a direct effect on attitudes toward rabies control (p-value <0.001 and 0.015). In brief, perceived benefits and the need for technology influence attitudes toward rabies control during the COVID-19 pandemic.